Strengthening Public Expenditure Efficiency Through System Integration: A Case Study of the Official Travel System in Indonesia - Afrizal Riswandha Akbar; Suprayitno (Universitas Muhammadiyah Yogyakarta, 2025)
The research intends to find how to redesign the official travel system which can mitigate the potential risks of inefficiency and fraud effectively by using business process improvement (BPI). The qualitative method is applied and business process improvement adopted as research strategy. The research object is XYZ and data collected from interviews, visits, observation, and documentary. Based on the results, a BPI model design for the official travel business process is created which has implications for increasing control through end-to-end processes by system and increasing business process time efficiency. The results mandate the government should integrate the official travel system with the other systems, including banking sectors, transportation and accommodation providers, and government expenditure system. The publications on how to redesign business process improvement of government expenditure to mitigate potential fraud risks of official travel expenditure system are still rare, whereas it is important to provide recommendations for government how to tackle such risks. Authors expect that the research could deliver contribution in mitigating the potential fraud risks of official travel